At the intersection of non-coding transcription, DNA repair, chromatin structure, and cellular senescence - Ohsawa, Ryosuke; Seol, Ja-Hwan; Tyler, Jessica K. (Frontiers in Genetics, 2013)
It is well accepted that non-coding RNAs play a critical role in regulating gene expression. Recent paradigm-setting studies are now revealing that non-coding RNAs, other than microRNAs, also play intriguing roles in the maintenance of chromatin structure, in the DNA damage response, and in adult human stem cell aging. In this review, we will discuss the complex inter-dependent relationships among non-coding RNA transcription, maintenance of genomic stability, chromatin structure and adult stem cell senescence. DNA damage-induced non-coding RNAs transcribed in the vicinity of the DNA break regulate recruitment of the DNA damage machinery and DNA repair efficiency. We will discuss the correlation between non-coding RNAs and DNA damage repair efficiency and the potential role of changing chromatin structures around double-strand break sites. On the other hand, induction of non-coding RNA transcription from the repetitive Alu elements occurs during human stem cell aging and hinders efficient DNA repair causing entry into senescence. We will discuss how this fine balance between transcription and genomic instability may be regulated by the dramatic changes to chromatin structure that accompany cellular senescence.